The Effect Of Sargassum sp. Liquid Organic Fertilizer In The Growth of Spinach Plant (Amaranthus hybridus L.) by Using Hydroponic - Syifa Fajrisani; Violita Violita; Irma Leilani Eka Putri; Des Des M (Bioscience, 2020)
Abstract. The purpose of this research to determined the effect of Sargassum sp. liquid organic fertilizer in the growth of spinach plant (Amaranthus hybridus L.) using hydroponic. This research used Completely Randomized Design with six treatments and four repetitions ie: A= comparison (AB mix 10 mL/L of water), B= liquid organic fertilizer 6 mL/L of water, C= liquid organic fertilizer 8 mL/L of water, D= liquid organic fertilizer 10 mL/L of water, E= liquid organic fertilizer 12 mL/L of water, and F= liquid organic fertilizer 14 mL/L of water. Parameter observed was height of plants, number of leaves, leaf surface area, fresh weight of plants, and dry weight of plants. Data was analyzed by using the Analysis of Variants (ANOVA)  and Duncan. The result showed that application of Sargassum sp. liquid organic fertilizer has been  an effect on height of plants, number of leaves, leaf area, fresh weight of plants, and dry weight of spinach plant (Amaranthus hybridus L.). However, the effect was not as expected to increase the growth of spinach plant.